Using AI in Translation, a Technological Leap, or a Translator’s Nightmare - Mohammed Tewfik BOUGUESMIA (Altralang Journal, 2020)
ABSTRACT: A dream to many, the idea of using machines for rapid, effortless, and accurate translation has allured both tech-enthusiasts and translation aficionados for a long time. Sadly, the technical limitations that inhibited computers from looking beyond the word, thus affecting their ability to offer much more than literal translations void of contextual meanings, have prevented that fantasy from becoming a reality. However, the recent rise of Artificial Intelligence (AI) has once again sparked interest in such utilization of technology. While admittedly still in its beta version, and still reliant on the contribution of translators for its enhancement, the primary results of the use of AI for translation look promising to say the least. As a result, a heated debate, buried for years, has re-emerged about whether this technological development represents a threat to the future employability of translators, or an opportunity to innovate the field of translation, and bring it to the digital age. The aim of this research is to investigate the awareness of the Algerian translation teachers of the advances made in this regard, capture their opinions regarding the matter, and report their willingness or reluctance to contribute in the development of this technology. Therefore, open-ended questionnaires are administered to 10 teachers from the Djillali Liabes university. The findings reveal a variety of viewpoints and attitudes towards the matter